Numerical Modeling and Stability Analysis of Surrounding Rock of Yuanjue Cave. (12th January 2021) - Meng, Zhigang; Fan, Fangzheng; Cui, Xuebin; Tao, Shu; Cao, Yi
Abstract : Yuanjue Cave, located in Big Buddha Bay, Mount Baoding, Dazu Rock Carvings Area, has extremely high historical, artistic, and religious value and is an important grotto cultural relic in China. Due to the cutting action of the fissures and weak interlayers, the South Cliff of Big Buddha Bay where Yuanjue Cave is located showed signs of instability. In order to fully evaluate the stability of the rock mass around the cliff where Yuanjue Cave is located, a three-dimensional geological model of the surrounding rock of Yuanjue Cave was established by using FLAC3D software, combined with three-dimensional scanning, fissure investigation, and indoor tests. The stability of the surrounding rock mass adjacent to Yuanjue Cave has been studied by precise numerical simulation, and the results of numerical simulation and monitoring have been compared and analysed. The results show the following: (1) The west of J10 fissure, above the mudstone interlayer, is the main deformation area. The cliff displacement increases gradually from the east to the west. The independent block above the corner has the largest free space displacement, and there is a risk of independent collapse. Special attention should be paid to the stability of this block. The displacement of the upper monitoring point of the cliff wall is significantly greater than that of the lower layer. (2) In the surrounding rock block in the adjacent area, the various concentrated stresses of the body are mainly located at the entrance of Yuanjue Cave, the height of the chest of the Zhengjue Buddha statue, and the lower mudstone erosion and reinforcement zone. Among them, the stress concentration in the erosion and reinforcement area under the Zhengjue Buddha statue is the largest. The conclusions obtained can provide a useful reference for the stability assessment of the surrounding rock of Yuanjue Cave.